Clinical InvestigationsDosimetric Improvements in Balloon Based Brachytherapy Using the Contura® Multi-Lumen Balloon (MLB) Catheter to Deliver Accelerated Partial Breast Irradiation - Vicini, Frank A; Douglas, Arthur; Todor, Dorin; Julian, Thomas; Lyden, Maureen (Journal of Contemporary Brachytherapy, 2010)
Purpose: Preliminary dosimetric findings in patients managed with the Contura® Multi-Lumen Balloon (MLB) breast brachytherapy catheter to deliver accelerated partial breast irradiation (APBI) on a multi-institutional phase IV registry trial were reviewed. Material and methods: CT-based 3D planning with dose optimization was performed for all patients. For the study, new ideal dosimetric goals were developed: 1) ≥ 95% of the prescribed dose (PD) covering ≥ 90% of the target volume (TV), 2) a maximum skin dose ≤ 125% of the PD, 3) maximum rib dose ≤ 145% of the PD, and 4) the V150 ≤ 50 cc and V200 ≤ 10 cc. The frequency of concurrently achieving these dosimetric goals using the Contura® MLB was investigated. Results: 194 cases were evaluable. Employing the MLB, all ideal dosimetric criteria were achieved in 76% of cases. Evaluating dosimetric criteria separately, 90% and 89% of cases met the new ideal skin and rib dose criteria, respectively. In 96%, ideal TV coverage goals were achieved and in 96%, dose homogeneity criteria (V150 and V200) were met. For skin spacing ≥ 5-7 mm, the median skin dose was 121% of the PD and when < 5 mm, the median skin dose was 124.4%. For rib distancees < 5 mm, the median rib dose was reduced to 136.4% of the PD. For skin spacing < 7 mm and distance to rib < 5 mm, the median skin and rib doses were concurrently limited to 121% and 142.8% of the PD, respectively. Conclusions: The Contura® MLB catheter provides potential improvements in dosimetric capabilities (i.e., reduced skin and rib doses and improved TV coverage) in many clinical scenarios.